2009
DOI: 10.1111/j.1540-8191.2008.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Kommerell's Diverticulum, Risk Factor for Aortic Dissection

Abstract: A 54-year-old man presented with sharp chest pain and hypertension. He was treated with intravenous antihypertensive with good control of the blood pressure. Chest X-ray showed widened mediastinum, and subsequent computed tomography scan of the chest demonstrated dissection of the descending thoracic aorta. It also showed an aberrant right subclavian artery with retrograde extension of dissection and Kommerell's diverticulum, which is dilatation at the origin of the aberrant subclavian artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Surgical treatment of aortic disease being associated with different branching patterns has been described mainly by different case reports, addressing Kommerell diverticuli or bovine aortic arches. 15,16,20,21 Our data revealed higher rates of concomitant intervention of the aortic arch in patients with aneurysm who display anomalous branch patterns. Especially patients with a bovine aortic arch undergo hemiarch replacement more frequently than patients without aortic arch anomalies (46% vs 34.6%; P ¼ .023).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Surgical treatment of aortic disease being associated with different branching patterns has been described mainly by different case reports, addressing Kommerell diverticuli or bovine aortic arches. 15,16,20,21 Our data revealed higher rates of concomitant intervention of the aortic arch in patients with aneurysm who display anomalous branch patterns. Especially patients with a bovine aortic arch undergo hemiarch replacement more frequently than patients without aortic arch anomalies (46% vs 34.6%; P ¼ .023).…”
Section: Discussionmentioning
confidence: 56%
“…In terms of potential associations of aortic arch anomalies and TAD, 2 case reports describe the presence of a Kommerell diverticulum in patients with acute aortic dissections. 15,16 Stone and colleagues 17 addressed treatment options of the right aberrant subclavian artery in a series of 24 patients. They concluded that the presence of a Kommerell diverticulum in these patients correlated with the need for intervention, whereas the presence of aberrant right subclavian artery alone could be safely followed medically.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the aberrant right subclavian artery arose directly from the aortic arch at an acute angle. According to the hemodynamic theory, there would be a greater shear force in the bloodstream[12,15]. The high blood flow rate in the aorta had a direct impact on the wall of the aberrant right subclavian artery, and the fragile and easily damaged wall caused by the congenital abnormality aggravated the damage.…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde dissection of the ascending aorta from the coronary arteries during PCI 5 and from the right common carotid artery during inadvertent Swan-Ganz catheter insertion 6 has been described. It has been associated with pregnancy 7 and Kommerell's diverticulum 8 . However, spontaneous retrograde dissection of the ascending aorta from the descending aorta has no known predisposing factors that would foretell a retrograde propagation of dissection.…”
Section: Discussionmentioning
confidence: 99%